Automated printing machine using Canon IP2770 - Fernandez, Jemmalou A.; Dela Cruz, King August L.; Garcia, Ramigil R. (2014)
The project study is a coin operated printing system that collects the payment of the user based on the number of pages of document to be printed. The system offers editing of file and a gray scaled printing in short bond paper which mostly used by the people. The system uses a canon iP2770 printer, Gizduino (mini) with ATmega168 as the microcontroller of the system, coin acceptor for the collection of payments, paper sensor for bond paper indicator when the system has less than 10 bond papers left in the sheet feeder of the printer and a computer for the installation of software for user interface.
The system works by inserting a removable storage device like USB Flash drives to the computer, then the user chooses the desired word document file. The software includes the page counter, coin counter and the editing of files. The user is asked to insert a coin that corresponds to the number of pages to be printed. The user must enter an exact amount; otherwise, it cannot give back the change. After inserting the exact amount, the user must click the print button to print the document. A message box will prompt saying "Please wait for the printed document" and it ends the transaction. The fact that the system is a new innovation the Automated Printing Machine using Canon iP2770 is also a good business venture that can minimize tasks in the printing process.
Keywords: Coin-operated machines